Penonton Festival Film di Yogyakarta - Suwarto, Dyna Herlina (FISIP Universitas Atma Jaya Yogyakarta, 2017)
This study explore the demography, behavior, the information needed and accessible media audience of the Festival Film Pelajar Jogjakarta (FFPJ), Festival Film Dokumenter (FFD) and Jogja-Netpac Asian Film Festival. A quantitative descriptive method using questionnaire through convenience survey was employed. Finding show that most of the festival attendees are teenagers and young people who study in university. JAFF’s audience is more heterogeneous compares to other festivals. Repeated visit is relatively low. The most influential information sources are: friends recommendation, website and social media. Most of the festivalgoers choose the festival programs carefully based on website information and catalogue message.